SEA CUCUMBER AS ANTICANCER AGENTS AND ITS DEVELOPMENT FOR FUNCTIONAL FOOD PRODUCTS - Ridhowati, Sherly; Zakaria, Fransiska Rungkat; Syah, Dahrul; Chasanah, Ekowati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Indonesia is popularly known as sea cucumber (teripang) exporter in the form of dried teripang. Commonly known as beche-de-mer or gamat, sea cucumber has long been used as medicine and food by Asian and Middle East people. Recent study  has shown that sea cucumbers contain active compounds that show potential health benefits and other biological properties such as antibacterial and antifungal products, anticoagulants, antihypertensives, immuno modulation, inhibitor of osteoclastogenesis. It was reported that sea cucumber posses aphrodisiacs, potentially improve immunity, anticancer and anticoagulation. Sea cucumber is also rich in collagen as a component of connective  tissue which can further be converted into smaller molecule and act as bioactive substances. This  review presents  the potential of sea cucumber as a functional food especially to prevent cancer and  strategy to develop sea cucumber-based functional food  by enzymatic hydrolysis and in vivo study.